A Comprehensive Study on the Synthesis and Micellization of Disymmetric Gemini Imidazolium Surfactants. Issue 4 (23rd May 2016) - Zhao, Xiaohui; An, Dong; Ye, Zhiwen
Abstract: Two groups of disymmetric Gemini imidazolium surfactants, [C14 C4 C m im]Br2 ( m = 10, 12, 14) and [C m C4 C n im]Br2 ( m + n = 24, m = 12, 14, 16, 18) surfactants, were synthesized and their structures were confirmed by 1 H NMR and ESI–MS spectroscopy. Their adsorption at the air/water interface, thermodynamic parameters and aggregation behavior were explored by means of surface tension, electrical conductivity and steady‐state fluorescence. A series of surface activity parameters, including cmc, γ cmc, π cmc, p C 20, cmc/ C 20, Γ max and A min, were obtained from surface tension measurements. The results revealed that the overall hydrophobic chain length ( N c ) for [C14 C4 C m im]Br2 and the disymmetry ( m/n ) for [C m C4 C n im]Br2 had a significant effect on the surface activity. The cmc values decreased with an increase of N c or m/n . The thermodynamic parameters of micellization (Δ G m θ, Δ H m θ, Δ S m θ ) derived from the electrical conductivity indicated that the micellization process of [C14 C4 C m im]Br2 and [C m C4 C n im]Br2 was entropy‐driven at different temperatures, but the contribution of Δ H m θ to Δ G m θ was enhanced by increasing N c or m/n . The micropolarity and micellar aggregation number ( N agg ) were estimated by steady‐state fluorescence measurements. The results showed that the surfactant with higher N c or m/n can form larger micelles, due to a tighter micellar structure.